Use of information and communication technology (ICT) by medical students - José Carlos Gomes Pereira; Lucas Pontes dos Santos; Cezar Augusto Muniz Caldas (Revista Brasileira de Educação Médica, 2021)
Abstract: Introduction: The central topic of the present study is the evaluation of Information and Communication Technology use by medical students, since this relationship has become inseparable from medical training and practice. Objective: To characterize the profile of Information and Communication Technology use among medical students, identifying which are the most frequently used, the possible stimuli and the main impediments to its use. Method: An observational and cross-sectional study was carried out by applying an electronic form on the Google Forms® platform, to students attending from the 1st to the 12th semester of undergraduate medical school. Results: Of the 216 participants, there was a predominance of females (60.6%), aged between 20-24 years (65.3%) and with a family income of less than 3 minimum wages (36.1%). The main device used by the participants was the smartphone (68.1%) and the most frequently used Information and Communication Technologies were text messaging apps (99.5%) and internet browsers (96.8%), while Medication Apps (48.1%) and Specialized Calculators (31%) were significantly less often used. The main benefit mentioned was the possibility of distance communication, while the main impediment was the issue of security. Conclusion: It was concluded that the use of technologies by medical students is quite frequent and varied, but purposeful training, by teachers and students, is necessary for better use of the available technologies.